Utilization of Village Land Potential for Community Social Life in Anjir Serapat Muara 1 Village - Ayu Fajriyah; Ersis Warmansyah Abbas; Mutiani Mutiani; Muhammad Rezky Noor Handy; Raihanah Sari; Jumriani Jumriani (Universitas Lambung Mangkurat, 2023)
The presence of land has different potential in each region. The various potentials of the land are of course accompanied by proper utilization. Anjir Serapat Muara 1 Village is part of the Barito Kuala Regency, in its development, it also demands developments in the land potential for optimal utilization, especially in the field of the social life of the community. Departing from this potential, this article discusses various land uses for the social life of the people who live in Anjir Serapat Muara 1 Village. documentation collection. Then the results of this study are presented in a descriptive discussion. The results of this study state that the land potential of Anjir Serapat Muara 1 Village includes physical and non-physical potential. The physical potential relates to the potential of the land, water potential, and climate potential of the village. As for the non-physical potential, it includes the social life of the people in Anjir Serapat Muara 1 Village. With the potential that this village has, of course, land use is not far from things that support people's lives in Anjir Serapat Muara 1 Village, such as land use for settlements, for community service facilities which include governance or health services as well as utilization for the social life of the community in the village.